ENGLISH TEACHER’SDIFFICULTIES IN TEACHING VOCABULARY TO STUDENTS WITH LEARNING DISABILITIES - LESTARI, ULVHA DWI; ERLINA, DIAN; SAPUTRA, EKO (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This study investigated teachers' difficulties in teaching English vocabulary to students with learning disabilities and how they overcame the situation at SLB C KaryaIbu Palembang. The researchers used qualitative research with a case study method. This study was conducted at SLB C KaryaIbu Palembang. Purposeful sampling was employed in selecting the English teacher, with the criteria that the subject had an educational background from a particular school and had taught students with a learning disability who has more qualified in learning. In collecting data, the researchers used semi-structured interviews. The data were analyzed by using the thematic analysis technique. The result of the study showed that the teacher at SLB C Karya Ibu Palembang had difficulties teaching English vocabulary to students with a learning disability and some strategies to deal with the problem, such as asking the students to remember English vocabulary, attracting the attention of students, controlling pronunciation of students, managing the learning time, and finding proper strategies.